Relation between HLA typing and clinical presentations in Systemic Lupus Erythematosus patients at Qassim region, Saudi Arabia - Wadi, Walid; Elhefny, Noor eldeen A.M.; Mahgoub, Essam H.; Almogren, Adel; Hamam, Khaled D.; Al –hamed, Hamad A.; Gasim, Gasim I. (International Journal of Health Sciences, 2014)
Abstract Background: Systemic lupus erythematosus (SLE) is a disease with diverse clinical presentations due to interaction between genetic and environmental factors. SLE is associated worldwide with polymorphisms at various loci, including the major histocompatibility complex (MHC), although inconsistencies exist among these studies. Aims:This study was carried out to investigate, the association of HLA-DRB1, DRB3, DRB4, DRB5, and DQB1 alleles in SLE patients and clinical presentations at Qassim, Saudi Arabia. Methods: Fifty one patients with SLE—84.3% of whom had kidney involvement—were studied in a case control study for HLA-DRB1,DRB3, DRB4, DRB5, and DQB1. HLA DRB3 allele frequency, were significantly higher in SLE patients compared to controls (P = 0.042). Results: It was found that HLA DRB4 (p = 0.025) frequency was increased in patients with serositis, increased frequency of HLA DQB1*3/5 among SLE patients with skin manifestations when compared to those without skin manifestations, with a p value of (0.018) and (0.038) respectively, frequency of HLA DRB1*4 alleles was increased among SLE patients with arthritis versus those without arthritis (p value 0.034), and also among SLE patients with hematological manifestations versus those without hematological manifestations, p value (0.026). Conclusion: As in other populations DRB3 is a susceptibility gene among Saudi SLE patients. There was an increased HLA DRB4 frequency with serositis, DQB1*3/5 skin manifestations, HLA DRB1*4 with arthritis, and hematological manifestations.